Tính năng lượng tự do hydrat hóa của chất tương tự axit amin bằng phương pháp động lực phân tử - Vận, Đặng Ứng; Mi, Nguyễn Họa (Vietnam Journal of Chemistry, 2014)
The paper deals with molecular dynamics calculation of solvation free energy of some amino acid side chain analogs in water by GROMACS software and following Dillgroup calculation procedure. We calculated the free energy for turning off the Lennard-Jones interactions of 8 amino acid analogs including methane/Ala, n-butan/Ile, isobutan/Leu, propane/Val, acetamid/Asn, p-cresol/Tyr, etanol/Thr and metanol/Ser represented with the OPLS-AA force field in TIP3P water models. We achieved a high degree of statistical precision in molecular dynamic simulations and by thermodynamic intergration method obtained the deviation of calculated free energy of hydration of about 0.02 - 0.60 kcal/mol from the experimental hydration free energy measurements of the same molecules.